METODE PENENTUAN ARAH KIBLAT DENGAN POSISI MATAHARI - Antoni Jamil (Istinbath : Jurnal Hukum, 2015)
Research on method of determining the Qibla direction has been done by the people of Indonesia. But studies conducted have not been studied in depth at a particular focus of study. In fact, if observed, facing the qibla is the absolute duty for every Muslim. For facing the Qiblah closely associated with the implementation of the prayers that are part of one of the pillars of Islam. It can be said unauthorized person's prayers when implemented in a position not facing the Qibla. The samples in this study using techniques purposivve sampling area, where the sample is based on certain considerations in addition based on the area, because the Indonesian territory is divided into three time zones, the three regions of the sampled population, while the region was taken purposively by considering geographical location, namely latitude and longitude. Based on the research conducted, it can be seen that the rasydhul Qiblah daily can not be converted because of the time difference is relatively large, rasydhul Qiblah daily can be made a fixed schedule as the schedule of prayer, the sun's position in the sense of the distance of the sun from the equator very influential on the time or the time the sun right leads to the direction of Qibla (rasydhul Qiblah), while the geographical location there is however relatively small influence.